2012
DOI: 10.1016/j.ssc.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distributed particle magnetic moments on the magnetization of NiO nanoparticles

Abstract: Magnetization of nanoparticles of NiO are measured and analyzed taking into account a distribution in particle magnetic moment. We find that disregarding this distribution in the analysis is the reason for the many anomalous observations reported on this system in the literature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
2
23
1
6
Order By: Relevance
“…For isothermal magnetization of nanopowder sample at T = 290 K it was found that the modified Langevin function is better than the classical Langevin in fitting experimental points, although even that fit is not quite satisfactory. One of the reasons might be a broad distribution of particle sizes and particle magnetic moments in 0.7(Fe 2 O 3 )/0.3(ZnO) nanopowder [15]. The effective magnetic moment of one Fe 3+ ion calculated from the obtained value of M S was only 0.5 Bohr magnetons what is well below for an expected value for spin-only magnetism of iron ion and thus it might be the evidence of the core-shell structure of investigated nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…For isothermal magnetization of nanopowder sample at T = 290 K it was found that the modified Langevin function is better than the classical Langevin in fitting experimental points, although even that fit is not quite satisfactory. One of the reasons might be a broad distribution of particle sizes and particle magnetic moments in 0.7(Fe 2 O 3 )/0.3(ZnO) nanopowder [15]. The effective magnetic moment of one Fe 3+ ion calculated from the obtained value of M S was only 0.5 Bohr magnetons what is well below for an expected value for spin-only magnetism of iron ion and thus it might be the evidence of the core-shell structure of investigated nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…his issue was addressed in the earlier paper by Ibrahim et al [34] based on the analysis by Richardson and Desai [35]and more recently by Silva et al [26] in connection with the data on ferrihydrite NPs. Since then, it has been applied to the magnetic properties of NiO NPs [36] and γ-Fe 2 O 3 NPs [11]. Analogous to the distribution in size given in Eq.…”
Section: Analysis Using Distribution Of Magnetic Momentsmentioning
confidence: 99%
“…К ним относит-ся проблема описания кривой намагничивания нанораз-мерных частиц материалов, которые в объемном виде обладают антиферромагнитным (AF) порядком [1][2][3][4][5][6]. В таких наночастицах, как правило, сохраняется AF порядок в " сердцевине"( " ядре"), но поверхностные эф-фекты и дефекты приводят к появлению нескомпен-сированного магнитного момента частиц µ P [6][7][8][9][10][11], а наличие оборванных химических связей в присутствии AF взаимодействий может являться причиной спин-стекольного поведения поверхностных атомов [10][11][12][13][14][15][16][17].…”
Section: Introductionunclassified
“…Во многих случаях корректное описание экспери-ментальных зависимостей M(H) AF частиц требует учета функции распределения по магнитным моментам частиц [8,[15][16][17][18][19]. В этом случае выражение (1) можно переписать в виде…”
Section: Introductionunclassified
See 1 more Smart Citation